A composition comprising nerve growth factor and 2-amino-1,1,3-tricyano-1-propene useful for the induction, stimulation, and maintenance of nerve growth, and methods of potentiating choline O-acetyltransferase and tyrosine hydroxylase by 2-amino-1,1,3-tricyano-1-propene are disclosed. - Da Vanzo, John Paul; Paul, Joseph W. (My University, 1997)
A composition comprising nerve growth factor and 2-amino-1,1,3-tricyano-1-propene useful for the induction, stimulation, and maintenance of nerve growth, and methods of potentiating choline O-acetyltransferase and tyrosine hydroxylase by 2-amino-1,1,3-tricyano-1-propene are disclosed.